2014
DOI: 10.1016/j.alcohol.2013.09.044
|View full text |Cite
|
Sign up to set email alerts
|

The alcohol-preferring (P) and high-alcohol-drinking (HAD) rats – Animal models of alcoholism

Abstract: The objective of this article is to review the literature on the utility of using the selectively bred alcohol-preferring (P) and high-alcohol-drinking (HAD) lines of rats in studies examining high alcohol drinking in adults and adolescents, craving-like behavior, and the co-abuse of alcohol with other drugs. The P line of rats meets all of the originally proposed criteria for a suitable animal model of alcoholism. In addition, the P rat exhibits high alcohol-seeking behavior, demonstrates an alcohol deprivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 87 publications
1
76
0
Order By: Relevance
“…Non-dependent alcohol use can escalate to a pattern of abuse that may be brought on by additional factors such as social pressure, age, genetic predispositions, and gender (Chassin et al, 2004; Oei and Morawska, 2004; Ceylan-Isik et al, 2010; Silveri, 2012). Many of these same factors influence drinking patterns in rodents, and these preclinical models have aided in the identification of some of the neural correlates of risky drinking (Anacker and Ryabinin, 2010; Sherrill et al, 2011; Gilpin et al, 2012; Karanikas et al, 2013; McBride et al, 2014). …”
Section: Animal Models Of Alcohol Use Abuse and Dependencementioning
confidence: 99%
“…Non-dependent alcohol use can escalate to a pattern of abuse that may be brought on by additional factors such as social pressure, age, genetic predispositions, and gender (Chassin et al, 2004; Oei and Morawska, 2004; Ceylan-Isik et al, 2010; Silveri, 2012). Many of these same factors influence drinking patterns in rodents, and these preclinical models have aided in the identification of some of the neural correlates of risky drinking (Anacker and Ryabinin, 2010; Sherrill et al, 2011; Gilpin et al, 2012; Karanikas et al, 2013; McBride et al, 2014). …”
Section: Animal Models Of Alcohol Use Abuse and Dependencementioning
confidence: 99%
“…The rederived P, NP, and HAD rats used here have been bred over many generations as a rodent model to investigate the genetic basis of excessive alcohol consumption by humans (Czachowski and Samson, 2002;McBride et al, 2014). These lines have been both behaviorally and neurobiologically characterized and show phenotypic differences in their responses to ethanol that may be of relevance to the neurogenetic mechanisms underlying ethanol preference or nonpreference (McBride et al, 2014).…”
Section: Cue-controlled Alcohol-seeking Behavioral Proceduresmentioning
confidence: 99%
“…These lines have been both behaviorally and neurobiologically characterized and show phenotypic differences in their responses to ethanol that may be of relevance to the neurogenetic mechanisms underlying ethanol preference or nonpreference (McBride et al, 2014). For example, P rats have a lesser aversive response to ethanol in a conditioned taste aversion procedure (Froehlich et al, 1988) and may show more anxiety-like behavior in an EPM compared with NP rats (Stewart et al, 1993), the latter observation being confirmed in the rP cohorts studied here, although this high-anxiety phenotype is not always observed (Viglinskaya et al, 1995).…”
Section: Cue-controlled Alcohol-seeking Behavioral Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Disparities in the effects of PDE4 inhibitors to alter EtOH drinking in the two rat lines could be associated with their distinct genetic backgrounds (cf. Bell et al 2012; McBride et al 2014). Thus, the innately higher expression levels of Pde4a and Pde4b in the NAc shell of P vs NP, but not HAD1 vs LAD1, rats observed in Exp 4 of the present study (Table 4) may indicate that the PDE4 system is more involved in EtOH intake by P vs HAD1 rats.…”
Section: Discussionmentioning
confidence: 99%